Tumor suppressor in lung cancer-1 (TSLC1) functions as a glioma tumor suppressor - Houshmandi, S.S. (2006)
Tumor suppressor in lung cancer-1 (TSLC1) loss is common in many human cancers, including meningioma. In this study, we demonstrate that TSLC1 protein and RNA expression is lost in 60% to 65% of high-grade gliomas, and that TSLC1 reintroduction into glioma cells results in growth suppression. Moreover, Tslc1 loss in mice results in increased astrocyte proliferation in vivo and in vitro. These data indicate that TSLC1 functions as a glioma tumor suppressor. ©2006AAN Enterprises, Inc.